2013
DOI: 10.1080/01419870.2013.783222
|View full text |Cite
|
Sign up to set email alerts
|

Segmented political assimilation: perceptions of racialized opportunities and Latino immigrants' partisan identification

Abstract: To account for Latino immigrants' assimilation into the American political mainstream, I derive social psychological factors from the contextual notion of 'modes of incorporation' in the segmented assimilation literature. These social psychological factors, perceptions of racialized opportunities (PROPs), relate to immigrants' adoption of political party identities (i.e. Democrat, Republican). I test these PROPs factors utilizing the 2006 Latino National Survey (N05,717 immigrant Latino respondents). Multinomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…In the same study, stronger identification with white opportunities was linked to opposition to government intervention in health care while stronger identification with black opportunities was linked to support for government intervention in health care. Samson (2014) also found that Latino immigrants who identify more strongly with white opportunities are more likely to politically identify as Republican, while Latino immigrants who identify more strongly with black opportunities are more likely to politically identify as Democrat than Republican, essentially rendering Republican and Democrat partisanship as ethnoracially related identities into which immigrants assimilate after arriving in the USA. Samson argues that whether ethnoracial group-differentiated structural opportunities do in fact exist as separate mobility pathways is less germane to the social psychological theory of PROPs than the fact that people perceive such trajectories exist and differ in meaningful ways.…”
Section: Modes Of Incorporation and Propsmentioning
confidence: 88%
See 4 more Smart Citations
“…In the same study, stronger identification with white opportunities was linked to opposition to government intervention in health care while stronger identification with black opportunities was linked to support for government intervention in health care. Samson (2014) also found that Latino immigrants who identify more strongly with white opportunities are more likely to politically identify as Republican, while Latino immigrants who identify more strongly with black opportunities are more likely to politically identify as Democrat than Republican, essentially rendering Republican and Democrat partisanship as ethnoracially related identities into which immigrants assimilate after arriving in the USA. Samson argues that whether ethnoracial group-differentiated structural opportunities do in fact exist as separate mobility pathways is less germane to the social psychological theory of PROPs than the fact that people perceive such trajectories exist and differ in meaningful ways.…”
Section: Modes Of Incorporation and Propsmentioning
confidence: 88%
“…First, a fuller test of the PROPs theory comparable to earlier tests among Latino samples would incorporate perceptions of shared economic commonality in addition to the political commonality measures utilised here (Samson 2012(Samson , 2014. While multiple item measures of an underlying construct are ideal, the survey only contained one item to operationalise perceived racialised opportunities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations